Physical, Optical, and Radiation Shielding Features of Yttrium Lithium Borate Glasses - Algarni, Saud A.; El-Maaref, A. A.; Alotaibi, B. M.; Alharbiy, Nuha; El-Rehim, A. F. Abd; Wahab, E. A. Abdel; Shaaban, Kh. S. (Journal of inorganic and organometallic polymers and materials, 2022)
Glass series with the composition 72 B 2 O 3 —( 28 - x ) Li 2 O— x Y 2 O 3 : x = 0, 2, 4,8, and 12 mol% was fabricated using the melt quenching procedure. The structural, optical, and radiation shielding characteristics have been estimated. As the concentration of Y 2 O 3 increased, the optical bandgap (direct and indirect), and refractive index of fabricated samples increased, while Urbach's energy declined. Dispersion parameters of the fabricated samples were determined. The gamma attenuation variables of manufactured samples were detected with the Phy-X/PSD code. The highest MAC values were found at low energies, indicating that it could be used as a gamma radiation absorber. G 1 presented the maximum MFP and HVL, while G 5 has the slightest MFPs and HVLs. Z eff v a l u e s decreases with an increase of Y 2 O 3 . So, these results indicate that G 5 has stronger photon shielding than the other glasses.